Employment status of women with disabilities from the Behavioral Risk Factor Surveillance Survey (1995-2002) - Smith DL (Work, 2007)
Among working aged adults (18-64) with disabilities, three out of 10 (32%) work full or part-time, compared to eight out of 10 (81%) of those without disabilities [9]. In addition, 24.7% of women with a severe disability and 27.8% of men with a severe disability are employed, while women with a non-severe disability have an employment rate of 68.4% and men with a non-severe disability have an employment rate of 85.1% [14]. This study examined data from the Behavioral Risk Factor Surveillance Survey from 1995-2002 to determine whether or not disparities exist in the rate of unemployment for women with disabilities, compared to men with disabilities and women and men without disabilities. In addition, regression analysis looked at the how disability and gender predict the outcome of unemployment. Results showed that there has been essentially no change with regard to employment for any of these populations. In addition, disability and gender were found to be the strongest predictors of unemployment for women with disabilities. Possible explanations were discussed as to the reasons for the results and issues were presented for future research.